Hubungan Endorsement oleh Influencer Tiktok dan Intensitas Menonton Tiktok Terhadap Perilaku Konsumtif Kaum Muda (Studi Kasus Gereja Di Denpasar) - Sinaga, Sry Rahayu; Zuryani, Nazrina; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 4 No 1 (2024): JISSOROT, 2024)
This study is motivated by the existence of social pressure in maintaining self-image and prestige in the consumptive behavior of church youth which is seen from its relationship with endorsement and intensity of watching TikTok. This study aims to determine how significant the relationship of endorsement by influencers and the intensity of watching TikTok is to consumptive behavior using Baudrillard's theory of consumption society. The method used is a quantitative paradigm with multi-stage sampling techniques to respondents totaling 239 people, namely church youth lin lDenpasar. In lorder to provel land thel lrelationship in data, the validity and reliability tests of the questionnaire items were used, determining the correlation coefficient (R), classical assumption test, multiple linear regression test as well as the F test and T test. The results of the t-test at a 5% margin of error show that endorsement by influencers is 1.182 and for the intensity of watching TikTok is 1.148. Likewise with the F test, where the F-test result is 21.123. The strength of the relationship formed is at a moderate level with an R of 0.578. While the regression equation model obtained is Y = 0.392 X1 + 1.015 X2. The resulting coefficient of determination is 33.4% which is the percentage contribution of variables X1 and X2 to Y. While the other 66.6% is explained by other factors, namely addiction to watching TikTok. Based on the results of this study, it is strongly recommended that the variable coefficients of endorsement by TikTok influencers and TikTok viewing intensity do not expand exponentially towards high intervals.